Efektivitas Layanan Satu Pintu dalam Meningkatkan Kualitas Pelayanan di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Hasanah, Sarah; Marlini, Marlini; Rahma, Elva (TSAQOFAH, 2026)
Improving service quality is an urgent necessity for libraries as public service institutions, particularly in the digital era. One of the innovations developed to address this need is the One-Stop Service model, which integrates various types of services into a single service channel. This study aimed to assess the effectiveness of the One-Stop Service in improving service quality at the Proklamator Bung Hatta Library Technical Implementation Unit (UPT) in Bukittinggi and to identify its impacts and the obstacles encountered in its implementation. A qualitative approach with a descriptive method was employed through in-depth interviews and observations involving five purposively selected informants, namely librarians and staff directly involved in service provision. The findings show that the implementation of a WhatsApp-based One-Stop Service has accelerated service processes, facilitated user access, improved the quality of interaction between librarians and visitors, and reduced delays in the return of library materials. Nevertheless, several challenges remain, including limitations of application features, the potential for misunderstandings in communication, and the influx of messages outside working hours. The study concludes that the One-Stop Service is effective in enhancing library service quality and constitutes a relevant innovation to support more responsive, user-oriented library services.